The effect of housing tenure on health status of migrant populations in China: are health service utilization and social integration mediating factors? - Fulin Jia; Xiaonan Liu; Yuxiang Wang; Mingze Ma (BMC, 2023)
Abstract Background Current research suggests that there is an association between housing tenure and the health status of migrant populations, but the potential mediators of this association remain to be explored. We aimed to examine the effect of housing tenure on migrant populations' health in China and how this effect is mediated by health service utilization and social integration. Methods Data from the 2017 China Migrants Dynamic Survey of 47,459 participants was used. Logistic regression models were used to explore the effects of housing tenure, health service utilization, and social integration on the health status of migrant populations. Mediated effects models were used to explore the association among them. This study used the bootstrap method and KHB method to test the mediating effect of health service utilization and social integration. Results Compared to private renters, owners with mortgages (OR: 0.828, 95% CI: 0.765-0.896) were significantly associated with a higher risk of poor health. Compared with private renters, outright owners were associated with a lower risk of poor health (OR: 1.016, 95% CI: 0.935, 1.104), but the association was not statistically significant (p > 0.05). Moreover, health service utilization (OR: 1.422, 95% CI: 1.268, 1.594) and social integration (OR: 4.357, 95% CI: 3.555, 5.341) were both significantly associated with a higher probability of good health (p < 0.001). Conclusion Among migrant populations, homeowners with mortgages had a lower likelihood of good health than private renters, while there was no significant difference in the health status between outright owners and private renters. Moreover, health service utilization and social integration mediate the effect of housing tenure on the health status of migrant populations. Policies and interventions can be designed to improve the health service utilization and social inclusion of migrant populations to reduce health disparities across housing tenure types.